The Surge in Censorship Impeding Intellectual Freedom: The Challenge and Possible Solutions - Karunawardhana, Ayesha (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
Though the library has transcended its role in many respects over time, its cardinal function remains to be the dissemination of information, and the rest of its roles have either derived from it or necessary extensions of it. As the cornerstone of libraries, Intellectual Freedom (IF) is inherently connected with the dissemination of Information. Hence, any curtailment to IF inevitably hinders the core of their functionality. With a recorded surge in various censorship attempts, IF has been in more turmoil over the past three years than ever. Per the latest statistics, censorship has increased in numbers, intensified tactically, and induced by violence with the hype of socio-political influences in the US. Also, inevitably, there are echoing incidents reported in Canada. This unusual amplification in numbers and virulent nature of censorship attempts has resulted in a drastic curtailment in the functionality of libraries, dwindling librarians’ capacities to uphold IF and ensure accessibility, inclusivity, and acceptance within library premises, resulting deprivation of the right to information and freedom of expression. This challenge has made the libraries self-interrogate how library professionals should uphold IF. While reflecting on the significance of IF and how censorship affects it, this study apprehends how this challenge affects the libraries and librarianship and its users in praxis and why it is a widespread, complicated, multi-faceted, and dilemma-packed issue to which finding a black-and-white answer is impossible. Arguing that this issue could be addressed only through research-backed, practical solutions, this paper presents some theoretical and pragmatic approaches that are worth adopting by librarians not only in upholding IF but also in enhancing inclusivity, accessibility, and acceptance. This qualitative research collates the contemporary knowledge on IF and censorship, as well as the legal and ethical frameworks pertinent to those notions and reflects on the statistical evidence available on the latest tendencies in censorship in the USA and reported similar incidents in Canada. Furthermore, in suggesting solutions, this study also sheds light on some interdisciplinary standpoints and certain generic approaches.